تجربة جامعة تشرين في تخزين الطاقة الشمسية بالطور الصلب (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تم تصميم وتصنيع مجمّع شمسي من مواد محليّة بالكامل وكذلك خزان شمسي يعمل باستخدام صخور محلية تم انتقاؤها بعناية بعد دراسة خواصها الحرارية، ثم وصل المجمّع مع الخزان بواسطة أنابيب هوائية معزولة بحيث يتم تدوير الهواء بواسطة مروحة كهربائية ضئيلة استهلاك الطاقة. جرت القياسات خلال 140 يوم من أواخر 2000 وحتى الشهر الثامن من 2001، وحيث تم حساب مردود التخزين الحراري خلال تلك الفترة.   A design and construction of a flat solar collector using air as a heat transport media, was made from wholly domestic materials collected from different places in Syria, with an isolated heat storage solid-state unit. Air was circulated by an electric motor with low energy consumption. Full measurements were carried out during 140 days (2000-2001) and thermal storage efficiency was calculated for that period.